Shifting to a Sustainable Dietary Pattern in Iranian Population: Current Evidence and Future Directions - Sobhani, Seyyed Reza; Omidvar, Nasrin; Abdollahi, Zahra; Al Jawaldeh, Ayoub (Frontiers in Nutrition, 2021)
The need for a shift in diet toward a more sustainable one has reached an urgency in certain regions, including Iran, due to more rapid climate change and a higher level of vulnerability. The present review was undertaken to identify and summarize available data on changes required in the current Iranian diet to make it more sustainable and the extent to which current policies in the country have addressed such a shift. In this scoping review, PubMed, Scopus, and Web of science, as well as Iranian scientific search engines, including Scientific Information Database and Magiran were systematically searched, from January 1990 to July 2021. A total of 11 studies and policy analyses were included in this review. Based on the findings, moving the Iraniannian diet toward sustainability will require, increase in consumption of dairy, fruits, vegetables, cereals, poultry, and legumes and a decrease in consumption of bread, rice, pasta, red meat, eggs, fats, sugars, and sweets. There has been a great deal of effort and investment on policies and strategies to decrease the amount of sugar, salt, and fat (specifically trans fatty acids) in the Iranian diet which makes it more sustainable healthwise. Several policies and programs have been implemented to tackle non-communicable diseases (NCDs) by reducing access to unhealthy foods which is in line with the health dimension of a sustainable diet. However, there is almost no direct address to the ecological aspect of sustainable diet in the food and nutrition policy documents in the country. The development of an enabling environment to a sustainable diet will require policy and actions to improve public awareness, support research to provide evidence and identify possible alternatives, and plan and implement interventions/programs to promote and facilitate healthy and sustainable diets.